2022
DOI: 10.17645/mac.v10i1.4737
|View full text |Cite
|
Sign up to set email alerts
|

Why Do People Return to Video Platforms? Millennials and Centennials on TikTok

Abstract: While some social networks like Facebook are losing interest among digital influencers, TikTok continues to grow, capturing and impacting centennials and millennials alike. This situation highlights the new generations’ increasing interest in short video formats, which are also becoming a new window of communication between companies and consumers. TikTok allows users to create, share, and discover short, user-generated videos in hopes of attracting viewers. But it is necessary to understand the variables that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 44 publications
3
28
0
3
Order By: Relevance
“…Figure 6 shows the percentage for Tik Tok usage frequency. The categories were replicated from (Cuesta-Valino, 2022). 75% claimed they used Tik Tok every day.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6 shows the percentage for Tik Tok usage frequency. The categories were replicated from (Cuesta-Valino, 2022). 75% claimed they used Tik Tok every day.…”
Section: Resultsmentioning
confidence: 99%
“…The short video length, however, was considered one of the drivers of success for the platform at its launch. In fact, for the Generation Z and Millennial users, that constitute the majority of the platform's audience, the short-form video format is what motivates them to continue using TikTok (Cuesta-Valiño et al, 2022). In addition, data from a survey conducted by the platform indicated that almost 50 percent of users found videos longer than a minute were stressful, with a third of users watching videos online at double speed (Stokel-Walker, 2022)…”
Section: Content By Professionals and Average Usersmentioning
confidence: 99%
“…The development of TikTok is still in its infancy. It is generally considered that the investigation into TikTok began in 2020 (Cuesta-Valino et al, 2022). Only a few studies attempt to adopt limited theoretical models to explore individuals' behavioral intentions in TikTok (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies attempt to adopt limited theoretical models to explore individuals' behavioral intentions in TikTok (e.g. purchase and adoption), including the uses and gratification (U&G) theory (Cuesta-Valino et al, 2022;Meng & Leung, 2021;Scherr & Wang, 2021), affordance theory (Song et al, 2021) and human-computer interaction theory (Wang, 2020), which mainly focus on the features of TikTok. For example, several researchers proposed TikTok affords several technological features such as live streaming, searching, meta-voicing (Song et al, 2021), personalized recommendation algorithms and easy-to-use editing (Du, Liechty, Santos, & Park, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation